Upregulation of MicroRNA‐126 Contributes to Endothelial Progenitor Cell Function in Deep Vein Thrombosis via Its Target PIK3R2. Issue 8 (August 2015) - Meng, Qingyou; Wang, Wenbin; Yu, Xiaobin; Li, Wendong; Kong, Lingshang; Qian, Aimin; Li, Chenglong; Li, Xiaoqiang
ABSTRACT Deep vein thrombosis (DVT) is a common complication of surgery. Endothelial progenitor cells (EPCs) are recruited into resolving venous thrombi. In this report, we investigated the effects of miR‐126 on EPCs function and venous thrombus resolution. We demonstrated that overexpression of miR‐126 enhanced EPCs' migration and tubulogenic activity in vitro, and promoted EPCs' homing and thrombus resolving in vivo. Moreover, we identified that miR‐126 directly targeted PIK3R2 and affected PI3K/Akt signaling axis. Overall, our findings demonstrated that miR‐126 promoted EPCs function through suppressing PIK3R2 expression and modulation of miR‐126 may represent a potential therapeutic intervention for treating DVT. J. Cell. Biochem. 116: 1613–1623, 2015. © 2015 Wiley Periodicals, Inc.